Consciousness emerging : the dynamics of perception, imagination, action, memory, thought, and language - Bartsch, Renate, 1939- (Advances in consciousness research, 2002)
This study of the workings of neural networks in perception and understanding of situations and simple sentences shows that, and how, distributed conceptual constituents are bound together in episodes within an interactive/dynamic architecture of sensorial and pre-motor maps, and maps of conceptual indicators (semantic memory) and individuating indicators (historical, episodic memory). Activation circuits between these maps make sensorial and pre-motor fields in the brain function as episodic maps creating representations, which are expressions in consciousness. It is argued that all conscious.